2019
DOI: 10.1038/s41598-019-40626-2
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide binds to ATP-binding pocket of VEGFR2 to impede VEGFA-mediated tumor-angiogenesis

Abstract: Vasculogenesis and angiogenesis are process of formation of blood vessels. Blood vessels are evolved to distribute nutrients and oxygen to distant organs. These vessels are crucial for growth and repair of wounded tissue. During tumor condition there occurs imbalance in the growth of blood vessels which leads to neo-angiogenesis. Neo-angiogenesis is major perpetrator behind the establishment of tumor. Tumor cells secrete pro-angiogenic factor VEGFA which binds to VEGFR2 present over surface of endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Previous studies have indicated that VEGF-A binds and activates receptor tyrosine kinase VEGFR2 on endothelial cells, triggering vascular growth and endothelial cell proliferation, migration, survival and increasing vascular permeability 27,[33][34][35] . The more VEGF molecules interact with VEGFR2, the stronger the promoting effect on blood vessels 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that VEGF-A binds and activates receptor tyrosine kinase VEGFR2 on endothelial cells, triggering vascular growth and endothelial cell proliferation, migration, survival and increasing vascular permeability 27,[33][34][35] . The more VEGF molecules interact with VEGFR2, the stronger the promoting effect on blood vessels 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the key interactions are three H-bonds (quinoline nitrogen and Cys 919 ; urea oxygen and Asp 1046 ; urea nitrogen and Glu 885 ), two hydrophilic interactions (the C-6 carboxamide with Asn 923 , bridged by water molecules) and several π-interactions (quinoline and C-4 phenoxy moiety with Leu 840 , Phe 818 and Lys 868 ) [ 130 ]. Quinoline core and urea moiety in tivozanib showed the same key interactions observed for the parent compound (PDB id: 4ASE) [ 131 , 132 ].…”
Section: Quinolines As Inhibitors Of Carcinogenic Pathwaysmentioning
confidence: 98%
“…Molecular-docking module and biochemical analyses have shown that andrographolide acts as a highly efficient docking molecule that binds effectively to ATP-binding pocket of VEGFR2 and interferes with its kinase activity [45].…”
Section: Regulation Of Vegf/vegfr Signalingmentioning
confidence: 99%